Effect of vitamin E and selenium on postpartum reproductive performance of buffaloes - Mavi, P S; Pangaonkar, G R; Sharma, R K (The Indian Journal of Animal Sciences, 2011)
Effect of exogenous administration of vitamin E and selenium during prepartum period on postpartum reproductive performance ofbuffalo was studied. Healthy MUITah buffaloes (5) were administered 500 mg ofvitamin Eand 15 mg of selenium, 2 weeks before the expected date of calving. In untreated control 6 buffaloes were kept. Treatment significantly reduced the expulsion time of foetal membranes. Majority of treated buffaloes (80.0%) took less than 30 days for complete involution of uterus while only 33.3% ofcontrol animals completed uterine involution within 30 days following calving. Treatment with vitamin E and selenium also led to early initiation of postpartum ovarian activity and carly exhibition of first postpartum heat. Duration of first progesterone rise of over I ng/ml of plasma was significantly longer in treated animals. Conception rate was significantly higher and service period was significantly less in treated buffaloes. Thus, vitamin E and selenium administration in prepartum buffaloes may result in bettcr concepton./>